PERANCANGAN ULANG ALAT BANTU JIG MENGGUNAKAN PENDEKATAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) DI CV. SEKEN LIVING - Anom Sadewo (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2021)
Assistive tools are useful tools to support the production process whose aim is to speed up work, to lighten the work. PT Seken Living is a company engaged in the manufacture of furniture and accessories that use the main material used teak wood, Overall process of producing divided into 4 process which is the material process, the assembly process, the finishing process and the packing process in each section has its own assistive tools used by workers.This study aims to redesign existing tools in the assembly section which is the wooden JIG tool that is used to provide marks for the work of making grooves. This aims to meet the needs of users of this instrument that is expected to ease and help the production process. Quality Function Development is a method that can transform user requests into a design quality also the ability to find out the priority attributes.The results of this study found that the attributes that are a priority or very influential for the tool development process is, the addition of a size indicator, the addition of an adjustable scratch, the addition of a bottom stop, and an additional grip for easy handling.Â Keywords: redesign, tools, products, quality function development, house of quality, user requests.